Prosaic mystery, pentimento images - Hettinga, Kathy T. (Kathy Tolsma), author; Dormer, James T., advisor; Orman, Jack L., committee member; Jordan, James R., committee member (Colorado State University. Libraries, 1985)
The idea began with depicting places/landscapes that I feel an emotional affinity for; this initial interest was in expressing, by the subject matter and the marks, the intense feeling of a certain place and my relationship to it. Beyond the landscapes, which involved the places that I had lived, I then felt it necessary to add the images of people that I had known, who were intimately and inextricably tied to these places. The figures and the structured landscapes were interwoven in overlapping structures, resulting in phantoms of remembered places and pentimento figures; some clearly delineated, others merging with the architecture, or fading into grass fields. These distanced symbols of passing people and places, I saw as embodying the temporal nature of life and thus something of our common mystery. In these prints, I strove to represent what is of importance to me, personal symbols of people and places filled with the personal moment, which is specific; and in this very specificity, embodies the universal.
Keywords: Prints, American